IT Governance Audit at District X Communications and Information Office Using COBIT 5 - friska trisnadewi; Gusti Agung Ayu Putri; Anak Agung Ngurah Hary Susila (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
Local government efforts to develop digitalization as a whole to outlying areas have been planned with several work programs in all regional apparatus organizations. District X Communications and Information Office is the center of information technology services in District X, it has an important role in serving the community related to regional digitization. Based on that role, it is necessary to have good governance to provide maximum community service. This research purpose is to measure the capability level of IT governance based on the work indicators in the strategic plan. Implementation of the COBIT 5 framework is used as a research method with domain constraints on DSS and BAI. The selection of the two domains is based on the mapping results that have been carried out following the goal cascade in COBIT 5. The research results obtained that the DSS01, BAI09, DSS02 process domains are achieved level 2, the DSS06, BAI08 process domains are achieved level 1. Expectations of level achievement in each process domain are at level 5, therefore recommendations are needed to make improvements to each process to be able to reach the desired level.Keywords: Temperature module, time module, microcontroller.